2005
DOI: 10.1056/nejmoa050043
|View full text |Cite
|
Sign up to set email alerts
|

Rocky Mountain Spotted Fever from an Unexpected Tick Vector in Arizona

Abstract: This investigation documents the presence of Rocky Mountain spotted fever in eastern Arizona, with common brown dog ticks (R. sanguineus) implicated as a vector of R. rickettsii. The broad distribution of this common tick raises concern about its potential to transmit R. rickettsii in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
287
2
26

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(327 citation statements)
references
References 24 publications
5
287
2
26
Order By: Relevance
“…The occurrence of five confirmed cases of BSF in this region and the lack of A. cajennense infected by R. rickettsii, until now, is in agreement with the data showed by Demma et al (2005) More publications have showed evidence that the brown dog tick is the RMSF vector in some regions of the USA, where close human interaction with free-roaming community dogs heavily parasitized by these ticks is observed. Also, in California, where the role of R. sanguineus is unclear as a potential vector of this disease, R. rickettsii was detected in this tick, but some differences in genotypes were shown between the strains isolated from Arizona, demonstrating a significant genetic diversity in this species of the spotted fever group rickettsiae SFGR (Wikswo et al 2007).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The occurrence of five confirmed cases of BSF in this region and the lack of A. cajennense infected by R. rickettsii, until now, is in agreement with the data showed by Demma et al (2005) More publications have showed evidence that the brown dog tick is the RMSF vector in some regions of the USA, where close human interaction with free-roaming community dogs heavily parasitized by these ticks is observed. Also, in California, where the role of R. sanguineus is unclear as a potential vector of this disease, R. rickettsii was detected in this tick, but some differences in genotypes were shown between the strains isolated from Arizona, demonstrating a significant genetic diversity in this species of the spotted fever group rickettsiae SFGR (Wikswo et al 2007).…”
Section: Resultssupporting
confidence: 90%
“…Nowadays, other species have been reported as A. triste (Venzal et al 2008) in Uruguay and Rhipicephalus sanguineus in the USA (Demma et al 2005, Wikswo et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector typically attributed with RMSF transmission and maintenance in the southeastern United States is Dermacentor variabilis (the American dog tick), 1 although the widely distributed Rhipicephalus sanguineus (the brown dog tick), is also found in Tennessee 2 and has been shown to transmit the pathogen in other parts of the country. 3,4 Tennessee historically reports one of the highest incidence rates for RMSF in the United States, 5,6 which have rapidly increased in recent years. In 2008, 224 cases were reported to the Tennessee Department of Health (TDH), a 20% increase over 2007 and 120% increase over 2004.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a human outbreak of Rocky Mountain spotted fever was reported in the White Mountain region of eastern Arizona in 2004. During this outbreak investigation, Rhipicephalus sanguineus was implicated as a vector for Rickettsia rickettsii, and the role of local dogs as short-term reservoirs and primary hosts for the vector tick was suggested because high prevalence of tick-borne pathogens in dogs from an Indian reservation in northeastern Arizona was reported [2,3] . Dogs …”
Section: Introductionmentioning
confidence: 99%